2021
DOI: 10.1007/s12325-021-01626-9
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Once-Monthly Paliperidone Palmitate on Healthcare Utilization Among Patients With Schizophrenia Treated in an Integrated Healthcare System: A Retrospective Mirror-Image Study

Abstract: Introduction Previous evidence demonstrated that patients with schizophrenia consumed substantial healthcare resources in an integrated healthcare system. This study evaluated the impact of initiating once-monthly paliperidone palmitate (PP1M) on healthcare resource utilization (HRU) among patients with schizophrenia treated in a US integrated healthcare system. Methods This retrospective study used electronic medical records from Atrium Health. Adults with at least two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 36 publications
(18 reference statements)
1
14
0
Order By: Relevance
“…A recent retrospective study of 210 patients with schizophrenia (mean age 34.2 years) based on the electronic medical records from Atrium Health in a US integrated healthcare system demonstrated a significant decrease in all-cause inpatient visits (67.6 to 22.4%, P < 0.001) and mean length of inpatient stay (14.2 ± 16.8 to 4.4 ± 13.2 days, P < 0.001) from the period before LAI initiation to 12 months after LAI initiation. Similar trends in mental health-related inpatient visits (67.6 to 22.4%, P < 0.001) and schizophrenia-related inpatient visits (61.4 to 20.5%, P < 0.001) were reported [ 40 ]. Another claim data study among US-based young adult Medicaid patients with schizophrenia reported 37% reduced all-cause inpatient admissions (odds ratio [OR], 0.63; 95% CI, 0.53–0.74) after initiating LAI compared to oral atypical antipsychotics cohort [ 29 ].…”
Section: Discussionsupporting
confidence: 73%
“…A recent retrospective study of 210 patients with schizophrenia (mean age 34.2 years) based on the electronic medical records from Atrium Health in a US integrated healthcare system demonstrated a significant decrease in all-cause inpatient visits (67.6 to 22.4%, P < 0.001) and mean length of inpatient stay (14.2 ± 16.8 to 4.4 ± 13.2 days, P < 0.001) from the period before LAI initiation to 12 months after LAI initiation. Similar trends in mental health-related inpatient visits (67.6 to 22.4%, P < 0.001) and schizophrenia-related inpatient visits (61.4 to 20.5%, P < 0.001) were reported [ 40 ]. Another claim data study among US-based young adult Medicaid patients with schizophrenia reported 37% reduced all-cause inpatient admissions (odds ratio [OR], 0.63; 95% CI, 0.53–0.74) after initiating LAI compared to oral atypical antipsychotics cohort [ 29 ].…”
Section: Discussionsupporting
confidence: 73%
“…Finally, only the study by [ 69 ] presented results on the effectiveness of LAI risperidone in a retrospective cohort study vs. all-oral SGAs and FGAs and vs. oral risperidone [ 69 ]. All the studies, including patients treated with PP1M, reported significant improvements in subjective well-being and global satisfaction, and improved personal and social performance [ 59 , 65 , 67 , 68 , 70 , 71 , 72 , 74 , 75 , 76 , 78 , 79 , 82 ]. Furthermore, functionality improvement was more remarkable in patients with a disease duration of 5 years or less [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, patients enrolled in other studies showed a low dropout rate, reduced acute healthcare use, and significantly improved neurocognitive function after 12 months of treatment with LAI SGAs, besides better effects on positive, negative, and affective symptoms, psychosocial functioning, and quality of life [ 79 , 82 ]. Furthermore, the transition from PP1M to PP3M evidenced a substantial decrease in combined medications and healthcare resource use, and increased adherence [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…The same can be said of the tolerability and safety, as the number of discontinuations is very low and corroborates previous research ( 32 , 34 ), some of them with a very similar mirror design. Also, the outcomes in the hospital resources used to follow the trend of similarly designed studies in other countries, in which a significant decrease in resources was found ( 35 ). Concerning measures of treatment adherence and compliance, and although this was measured in the current study considering the proportion of patients that discontinued PP1M—a very low proportion—results follow previously published evidence ( 36 ).…”
Section: Discussionmentioning
confidence: 99%